Targeted Gene Insertion for Functional CFTR Restoration in Airway Epithelium - Barillà, Cristina; Suzuki, Shingo; Rab, Andras; Sorscher, Eric J.; Davis, Brian R. (Frontiers in Genome Editing, 2022)
Cystic Fibrosis (CF) is caused by a diverse set of mutations distributed across the approximately 250 thousand base pairs of the CFTR gene locus, of which at least 382 are disease-causing (CFTR2.org). Although a variety of editing tools are now available for correction of individual mutations, a strong justification can be made for a more universal gene insertion approach, in principle capable of correcting virtually all CFTR mutations. Provided that such a methodology is capable of efficiently correcting relevant stem cells of the airway epithelium, this could potentially provide life-long correction for the lung. In this Perspective we highlight several requirements for efficient gene insertion into airway epithelial stem cells. In addition, we focus on specific features of the transgene construct and the endogenous CFTR locus that influence whether the inserted gene sequences will give rise to robust and physiologically relevant levels of CFTR function in airway epithelium. Finally, we consider how in vitro gene insertion methodologies may be adapted for direct in vivo editing.